2023
DOI: 10.1186/s13578-023-01147-8
|View full text |Cite
|
Sign up to set email alerts
|

A SNARE protective pool antagonizes APOL1 renal toxicity in Drosophila nephrocytes

Jin-Gu Lee,
Yulong Fu,
Jun-yi Zhu
et al.

Abstract: Background People of Sub-Saharan African ancestry are at higher risk of developing chronic kidney disease (CKD), attributed to the Apolipoprotein L1 (APOL1) gene risk alleles (RA) G1 and G2. The underlying mechanisms by which the APOL1-RA precipitate CKD remain elusive, hindering the development of potential treatments. Results Using a Drosophila genetic modifier screen, we found that SNARE proteins (Syx7, Ykt6, and Syb) play an important role in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…We previously showed that APOL1-G0 expression in nephrocytes induced toxicity, albeit less severe compared to APOL1-G1 18,32 . When we reduced the expression level of APOL1-G0 in nephrocytes by lowering the temperature to 22°C, APOL1-G0 toxicity was eliminated 33 ; hence all current fly experiments were conducted at 22°C (instead of 25°C used in our previous study) so that only APOL1-G1 remains toxic. Nevertheless, we found that Nef could also synergize with APOL1-G0, making it toxic at 22°C (Figure 1), consistent with clinical studies showing that people of West African genetic ancestry living with a high HIV viral load can develop HIVAN even if they do not carry an APOL1-RA 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that APOL1-G0 expression in nephrocytes induced toxicity, albeit less severe compared to APOL1-G1 18,32 . When we reduced the expression level of APOL1-G0 in nephrocytes by lowering the temperature to 22°C, APOL1-G0 toxicity was eliminated 33 ; hence all current fly experiments were conducted at 22°C (instead of 25°C used in our previous study) so that only APOL1-G1 remains toxic. Nevertheless, we found that Nef could also synergize with APOL1-G0, making it toxic at 22°C (Figure 1), consistent with clinical studies showing that people of West African genetic ancestry living with a high HIV viral load can develop HIVAN even if they do not carry an APOL1-RA 4 .…”
Section: Discussionmentioning
confidence: 99%
“…A majority of genes associated with kidney diseases have functional homologs in flies that are required for nephrocyte function 23,27 . The Drosophila nephrocyte has been well-established to study the pathogenesis of APOL1 -associated nephropathies 18,25,26,32,33 . Here, we generated Tg flies that express HIV-1 nef and APOL1-G1 , the most frequent risk variant, specifically in nephrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathways of injury have been proposed on the basis of studies using in vitro and in vivo models. These pathways include: impaired endo-lysosomal acidification, inhibition of autophagy and mitophagy, mitochondrial dysfunction, activation of inflammatory pathways (protein kinase R (PKR) activation, and Nod-like receptor protein 3 (NLRP3)/stimulator of interferon genes (STING) pathway, cytoskeletal perturbations, lipotoxicity, endoplasmic reticulum (ER) stress and inhibition of APOL3 modulation of PI4KB with impairment of mitochondrial fission and fusion and consequent cytoskeletal dysfunction [10–17,25,26,27 ▪ ,30–39]. Given the multiplicity of such pathways, a seminal question relates to the proximate step initiating injury, whose inhibition might prove to be most specific for therapy.…”
Section: Mechanism Of Apol1 Injury – New Insights and Unresolved Ques...mentioning
confidence: 99%
“…Putative explanations which can tie together heterozygous worse than hemizygous kidney injury in preclinical models, and a sharply nonlinear RRV dose profile in human studies, involve proposed augmented loss of auto-inhibition of APOL1 C-terminus mediated injury by intra - or inter - cellular N-terminus, or interaction of RRV with a protective element that is hindered in the presence of APOL1 G0 [ 25 ]. This would require that APOL1 G0 displays a greater binding affinity for this interaction, as was demonstrated for the soluble N -ethylmaleimide-sensitive-factor attachment protein receptor (SNARE) proteins [ 26 , 27 ▪ ]. These data imply that the dose effect is just part of the puzzle, and that moderating regulatory interactions are likely to better explain the partial penetrance and nonlinear risk of kidney disease with APOL1 RRV expression and resulting apparent recessive mode of risk inheritance.…”
Section: Mode Of Inheritance – Dose Effect Of Injurious Apo...mentioning
confidence: 99%
“…As a therapeutic perspective against this disease, disruption of APOL1 G1/G2 hydrophobic interactions with APOL3 could be attempted using either synthetic peptides of the interacting helices, lipid droplets [ 84 ] or overexpressed VAMP8 [ 85 ]. Alternatively, given the relative absence of dysfunctional phenotype in APOL1 KO cells [ 11 , 16 , 86 ], APOL1 inactivation could treat the disease [ 32 , 87 , 88 ].…”
Section: Concluding Remarks: Kidney Disease and Other Perspectivesmentioning
confidence: 99%